2017
DOI: 10.1007/s12012-017-9424-0
|View full text |Cite
|
Sign up to set email alerts
|

Asiatic Acid Ameliorates Doxorubicin-Induced Cardiac and Hepato-Renal Toxicities with Nrf2 Transcriptional Factor Activation in Rats

Abstract: Asiatic acid (AA), a pentacyclic triterpenoid, is a key phytoconstituent of Centella asiatica. AA is a patented as a cytotoxic substance, and it exerts cytotoxicity against Hep3B, Hela and MCF-7 cell lines. However, pentacyclic triterpenoids also modulate the expression and transcriptional activities of Nrf2 and exert cytoprotective effects. In this study, we investigated the effects of AA on the doxorubicin (DXR)-induced organ toxicities and expression of the Nrf2. DXR toxicity was induced by a single intrave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 33 publications
4
35
0
Order By: Relevance
“… 10 , 32 , 33 In addition, several studies have reported that AA could activate Nrf2 pathways to exhibit antioxidant and anti-inflammatory activities. 34 , 35 In the current study, AA markedly increased the expression level of nuclear Nrf2 as compared to the model group. Furthermore, the expressions of Nrf2-target proteins HO-1, NQO-1, and GCLC were increased in the AA-treated group.…”
Section: Discussionsupporting
confidence: 52%
“… 10 , 32 , 33 In addition, several studies have reported that AA could activate Nrf2 pathways to exhibit antioxidant and anti-inflammatory activities. 34 , 35 In the current study, AA markedly increased the expression level of nuclear Nrf2 as compared to the model group. Furthermore, the expressions of Nrf2-target proteins HO-1, NQO-1, and GCLC were increased in the AA-treated group.…”
Section: Discussionsupporting
confidence: 52%
“…These NRF2 targets, and others, are known to be induced by multiple compounds found in CA. Compounds such as the phenolic ferulic acid [89,90] and the triterpene asiatic acid [2,91], induce Nrf2 and its ARE-regulated targets, exhibiting a neuroprotective effect [92][93][94][95]. Caffeoylquinic acids found in CA [28,96,97], are also known to induce Nrf2 and Ho-1 signaling, and positively impact glutathione levels [98,99].…”
Section: Discussionmentioning
confidence: 99%
“…Increased activities of carbonic anhydrase II is associated with cardiac hypertrophy and heart failure. In another study, AA attenuated doxorubicin-induced oxidative stress and inflammation in the heart, liver, and kidney by upregulating Nrf2 protein expression (Kamble and Patil, 2018 ). Recently, AA showed to inhibit pressure overload or angiotensin II induced hypertrophic responses by suppressing collagen accumulation mediated cardiac fibrosis (Ma et al, 2016 ).…”
Section: Asiatic Acid In Cardiac Hypertrophymentioning
confidence: 99%